Acceptability of Malaysian working adults towards MOH chatbot services in disseminating COVID-19 information / Raja Anez Intantiana Raja Abd Aziz and Norzuraiza Rina Ahmad - Raja Abd Aziz, Raja Anez Intantiana; Ahmad, Norzuraiza Rina (Faculty of Information Management, 2023)
Chatbots have been popularly used nowadays as virtual conversational agents. With the latest technology facilities such as Human-Computer Interaction (HCI), Artificial Intelligence (AI), and Natural Language Processing (NLP), a chatbot can understand human language and becoming a thing now, especially after the existence of the pandemic COVID-19. The health sectors have changed ever since, and the rise of telehealth has taken place between physical interaction among health practitioners and patients. It has shifted to a chatbot medium for interaction to reduce the transmission of the disease. In line with the WHO's efforts, the Ministry of Health (MOH) Malaysia has taken initiatives to introduce and implement the chatbot facility to disseminate the latest information among Malaysians. This paper presents the findings of the acceptability of Malaysian, especially the working adults, since they are the most infected groups by the disease, and their willingness to use the MOH chatbot services. The findings are crucial for the apps developer, policy maker and the government (MOH), in order to develop the most efficient chatbot that will serve the intended purposes, so the initiative would not go wasted. The outcomes are hoped to provide insights into current health chatbot usage and acceptance, as well as any recommendations for future research in this field to address identified challenges.